2014
DOI: 10.1128/jvi.03443-13
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Stimulated Poly(ADP-Ribose) Polymerases Are Potent Inhibitors of Cellular Translation and Virus Replication

Abstract: The innate immune response is the first line of defense against most viral infections. Its activation promotes cell signaling, which reduces virus replication in infected cells and leads to induction of the antiviral state in yet-uninfected cells. This inhibition of virus replication is a result of the activation of a very broad spectrum of specific cellular genes, with each of their products usually making a small but detectable contribution to the overall antiviral state. The lack of a strong, dominant funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
190
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(192 citation statements)
references
References 58 publications
2
190
0
Order By: Relevance
“…However, the link between this posttranslational modification and translational arrest is difficult to establish. In a previous study, a mutant form of PARP12, lacking a putative autoribosylation site has been generated based on sequence homology with an experimental validated site found on PARP10 (19). Although the catalytic activity of this mutant protein was not evaluated, the authors concluded from their studies that mutants lacking a catalytic activity and/or displaying a modified automodification site were equally inefficient in mediating translational arrest.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the link between this posttranslational modification and translational arrest is difficult to establish. In a previous study, a mutant form of PARP12, lacking a putative autoribosylation site has been generated based on sequence homology with an experimental validated site found on PARP10 (19). Although the catalytic activity of this mutant protein was not evaluated, the authors concluded from their studies that mutants lacking a catalytic activity and/or displaying a modified automodification site were equally inefficient in mediating translational arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, overexpression of PARP12 led to a general translation arrest in BHK-21 (19) and HEK293T cells (this study). The ZnF-containing domain played an important role in addressing PARP12 to SGs, as shown by altered localization of PARP12 mutant lacking the ZnF domain and of the fourth ZnF point mutated forms (see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RNaseL -/-mice exhibit higher WNV viral loads in peripheral tissues. Members of the poly (ADP-ribose) polymerase family block translation and replication of VEEV [130,131]. IFN-induced transmembrane protein family members play a key role in limiting bunyavirus, including RVFV and LACV, replication by inhibiting viral membrane fusion in the endosome [132].…”
Section: Mechanisms Of Peripheral Infection Pathogenesis and Host Dmentioning
confidence: 99%